Nanostructures and thin films of transparent conductive oxides studied by perturbed angular correlations. Issue 4 (3rd April 2013) - Barbosa, M. B.; Gonçalves, J. N.; Redondo‐Cubero, A.; Miranda, S. M. C.; Simon, R.; Kessler, P.; Brandt, M.; Henneberger, F.; Nogales, E.; Méndez, B.; Johnston, K.; Alves, E.; et al.
Abstract The versatility of perturbed angular correlations (PAC) in the study of nanostructures and thin films is demonstrated, namely for the specific cases of ZnO/CdxZn1−xO thin films and Ga2O3 powder pellets and nanowires, examples of transparent conductive oxides. PAC measurements as a function of annealing temperature were performed after implantation of 111mCd/111Cd (T1/2 = 48 min) and later compared to density functional theory simulations. For ZnO, the substitution of Cd probes at Zn sites was observed, as well as the formation of a probe‐defect complex. The ternary CdxZn1−xO (x = 0.16) showed good macroscopic crystal quality but revealed some clustering of local defects around the probe Cd atoms, which could not be annealed. In the Ga2O3 samples, the substitution of the Cd probes in the octahedral Ga‐site was observed, demonstrating the potential of ion‐implantation for the doping of nanowires.